2013
DOI: 10.1007/s00432-013-1527-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chemotherapy and radiotherapy in childhood on fertility in adulthood: the FeCt—survey of childhood cancer survivors in Germany

Abstract: Patients and families need to be informed about fertility-preserving measures prior to and also after chemotherapy and radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 24 publications
0
37
0
3
Order By: Relevance
“…О р и г и н а л ь н ы е и с с л е д о в а н и я / О б з о р ы л и т е р а т у р ы за выявлены и у подростков, получавших лечение по поводу ОЛЛ [38], сарком [39], опухолей центральной нервной системы [40]. Гистологические исследования образцов тестику-лярной ткани подростков, получавших лечение в пре-пубертатный и пубертатный периоды, выявили апла-зию герминативного эпителия [41,42].…”
Section: гонадотоксичность противоопухолевой терапии у подростковunclassified
“…О р и г и н а л ь н ы е и с с л е д о в а н и я / О б з о р ы л и т е р а т у р ы за выявлены и у подростков, получавших лечение по поводу ОЛЛ [38], сарком [39], опухолей центральной нервной системы [40]. Гистологические исследования образцов тестику-лярной ткани подростков, получавших лечение в пре-пубертатный и пубертатный периоды, выявили апла-зию герминативного эпителия [41,42].…”
Section: гонадотоксичность противоопухолевой терапии у подростковunclassified
“…These institutions, referred to as data providers (DPs), provide data from 16 different institutional cohorts in total. Some of these DPs have previously collected their data, as part of a local fertility study [3,8,[17][18][19][20][21], while other DPs collect their data specifically during the PanCareLIFE project. All survivors included in the PanCareLIFE female fertility cohort study are treated between 1963 and 2014.…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, the number of childhood cancer survivors (CCSs) has substantially increased, and many of them have reached an age at which they consider parenthood. However, a compromised reproductive function is an important and frequently encountered late effect of treatment in female cancer survivors, with a high impact on quality of life [2][3][4]. Alkylating chemotherapy and radiotherapy involving the ovaries have been identified as the two main risk factors for fertility impairment, and post-pubertal treatment seems to be more gonadotoxic than pre-pubertal treatment [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Childhood radiotherapy increases the risk of damage to the hypothalamus and pituitary gland, decreasing the pituitary gonadotropins with subsequent ovaries dysfunction and highly likely leading to infertility. In Simone Reinmuth's epidemiological study, women treated with radiotherapy during childhood showed high rate of infertility (31 %) [3]. The human oocyte is exquisitely sensitive to radiation.…”
Section: Introductionmentioning
confidence: 99%